Swear Word Usage and Linguistic Expression in South Korean Hangug-eo: A Sociolinguistic Analysis - Mahayoni, Ni Putu Sukma; Budasi, I Gede; Mahendrayana, I Gede (Universitas Pamulang, 2025)
This study investigates the use of swear words by South Koreans, particularly those residing or traveling in Bali, Indonesia. It adopts a descriptive qualitative design to identify the forms, functions, and references of swear words used in the Korean language (Hangugeo). Data were collected through semi-structured interviews with both primary and secondary informants, including South Korean tourists and expatriates. The study employs the Miles and Huberman (1994) model for data analysis, which includes data reduction, display, and conclusion drawing. The findings reveal that 26 swear words are commonly used by South Koreans, categorized into monomorphemic (8), polymorphemic (17), and phrase forms (2). Functionally, the words are distributed across five categories: expletives, abusive, humoristic, euphemistic, and habitual usage. Additionally, the study classifies these swear words into eight reference categories: circumstance, animal, object, body part, kinship, spirit, activity, and profession. The results highlight that swearing in Korean serves not only as emotional release or aggression but also functions in humor and habitual speech. Moreover, the findings underscore the importance of cultural sensitivity in intercultural communication, as swear words can be easily misunderstood across linguistic and cultural boundaries. In multicultural settings such as Bali, where Korean tourists frequently interact with locals, misinterpretations of such expressions can lead to social tension. Therefore, this research emphasizes the need for heightened awareness of sociolinguistic differences to foster respectful and effective communication in globalized environments.